Interleukin‐18 and Interferon Gamma Levels in Preeclampsia: A Systematic Review and Meta‐analysis. (25th July 2014) - Yang, Yan; Su, Xiaowei; Xu, Wenming; Zhou, Rong
<x xml:space="preserve">Abstract</x> Problem This systematic review and meta‐analysis aimed to investigate the relationship between preeclampsia (PE) and circulating interleukin‐18 (IL‐18) and interferon gamma (IFN‐γ). Method of study Three electronic databases (PubMed, EMBASE, and Web of Science) were searched. Results Eleven studies with 947 participants reporting IL‐18 and 16 studies with 2230 subjects reporting IFN‐γ were included. There was no significant difference in the IL‐18 levels in PE patients compared with controls. However, IFN‐γ was found to be significantly higher in women with PE than that in normotensive pregnant women (standardized mean difference = 0.93; 95% confident interval: 0.07, 1.79). Furthermore, stratification by specimen type, quality score, method of estimation of mean and standard deviation, and whether sampling not in labor/premature rupture of membrane/infection also showed significant differences in standardized mean difference of IL‐18, as well as IFN‐γ. Conclusion This meta‐analysis suggests that circulating higher IFN‐γ levels may be associated with preeclampsia.